Klasifikasi dan Identifikasi Topeng Sandur Manduro dari Grup “Gaya Rukun” di Desa Manduro Kabupaten Jombang - Dyva Agnecia; Lilik Indrawati; Agnisa Maulani Wisesa (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: Sandur Manduro is a performing art in the form of a traditional theater which includes music, dance, fine arts, theater, and literature. Research on the Sandur Manduro Mask art from the "Gaya Rukun" group is deemed necessary because this group is the only Sandur group in Jombang Regency. Because the art of the sandur manduro mask is a banner instrument, the sandur mask figure has differences in its characteristics. This research seeks to; (1) classify the visuals of the Sandur Manduro mask in the "Rukun Style" group, (2) identify the visuals for the Sandur Manduro mask in the "Rukun style" group, using a descriptive research design. Data collection techniques used the method of observation, interviews, and document analysis. From the results of the study, it was found that the visualization of the protagonist and antagonist roles in Sandur Manduro's mask had differences in the color, nose shape, eyebrows shape, moustache shape and decoration. Meanwhile, the visualization of the role of the supporting character on Sandur Manduro's mask has similarities with the protagonist's role in addition to the color of the face which has two colors, namely red and white. Keywords: Visual classification, visual identification, masks, performing arts Abstrak: Sandur Manduro adalah seni pertunjukan berbentuk teater tradisional yang di dalamnya mengandung seni musik, seni tari, seni rupa, teater dan sastra. Penelitian tentang kesenian Topeng Sandur Manduro dari grup “Gaya Rukun” ini dirasa perlu dilakukan karena grup ini merupakan satu-satunya grup Sandur yang ada di Kabupaten Jombang. Karena kesenian Topeng Sandur Manduro merupakan instrument Panji tokoh topeng Sandur memiliki perbedaan pada karakteristiknya. Penelitian ini berupaya untuk; (1) mengklasifikasi visual Topeng Sandur Manduro grup “Gaya Rukun, (2) mengidentifikasi visual Topeng Sandur Manduro grup “Gaya Rukun, dengan memanfaatkan rancangan penelitian deskriptif. Teknik pengumpulan data dengan metode observasi, wawancara, dan analisis dokumen. Dari hasil penelitian ditemukan bahwa visualisasi peran protagonis dan antagonis pada Topeng Sandur Manduro memiliki perbedaan yang terdapat pada warna, bentuk hidung, bentuk alis, bentuk kumis dan ragam hias. Sedangkan visualisasi pada peran tokoh pembantu pada Topeng Sandur Manduro memiliki kemiripan dengan peran protagonis selain warna muka yang memiliki dua warna yaitu merah dan putih. Kata-kata kunci: klasifikasi visual, identifikasi visual, topeng, seni pertunjukan